MODERN APPROACH TO INFLAMMATORY DESEASES ETIOPATHOGENESIS OF PANCREAS - Pelipenko, L.B.; Yeroshenko, G.A. (World of Medicine and Biology, 2014)
The main forms of acute surgical diseases of the abdominal cavity acute pancreatitis occupy third place (12%) after acute appendicitis (58%) and acute cholecystitis (20%). Women suffer from three to four times more often than men, mostly aged 30-60 years. Total mortality in acute pancreatitis ranges from 15 to 23%, often with destructive complications. Disease is polietiologic. In pancreatic tissue occurring proliferation of connective tissue fibrosis and sclerosis. Last is both peri- and interacinar with simultaneous atrophy of the glandular tissue. As a result of intensive development of connective tissue changes volume of gland. Microscopically simultaneously with tissue fibrosis and inflammatory infiltration observed, lipomatosis, inflammatory changes in the walls of the ducts. Sometimes define obliteration of the ducts, the deposition of calcium salts in the tissues of gland.
Keywords: pancreas; inflammatory disease pathogenesis